Optimalisasi Potensi Masyarakat melalui Edukasi Digital bagi Pelaku UMKM di Wilayah Kabupaten Sumbawa secara Berkelanjutan - Zulkieflimansyah Zulkieflimansyah; Muammar Khadafie (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
Digitalization has become a necessity across all sectors, in line with the rapid development of digital technology and the shift towards Society 5.0. The use of digital technology is now a crucial aspect in various activities, including the economic, social, and educational sectors. In the economic sector, in particular, the implementation of electronic data interchange (EDI) and the use of social media in marketing strategies have expanded to various business sectors, including micro, small, and medium enterprises (MSMEs). The shift in interaction patterns between consumers and sellers towards digital is both a challenge and an opportunity for MSMEs. However, the reality on the ground shows that most MSMEs in the regions, particularly in Sumbawa Regency, still experience gaps in digital literacy and human resource readiness in managing information technology. To address this challenge, digitalization outreach and training activities are being conducted for MSMEs and the general public in the region. These activities aim to improve understanding and basic skills related to the use of digital technology in running and developing businesses, such as online marketing, digital data management, and the use of e-commerce platforms. This outreach also emphasizes the importance of adapting to technological developments to increase the competitiveness and sustainability of MSMEs in the digital era. The results of this activity showed a 3% increase in participants' understanding of digitalization, as evidenced by a comparison of pre-test and post-test results. While this improvement is initial and modest, it reflects positive changes that can be further developed through follow-up programs and ongoing mentoring. Therefore, community empowerment through digital education is a strategic step in strengthening the role of MSMEs as key drivers of the local and national economy in the digital era.